EFFICIENCY ASSESSMENT OF ELECTRICAL STIMULATION SIGNALS ON THE BASE OF TIME-FREQUENCY ANALYSIS OF STIMULATED MUSCLE GLOBAL ELECTROMYOGRAM - M. M. Mezhennaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method of physiological efficiency assessment of electrical stimulation signals signals with various parameters on the base of time-frequency analysis of stimulated muscle global electromyogram is developed. As criterion of efficiency it is offered to use an indicator of relative change of ratio of amplitude to effective bandwidth frequency of global electromyograms registered before and after electrical stimulation. The above described method is used for the efficiency assessment of rectangular bipolar signals with frequency of 50-1000 Hz and the sinusoidal modulated currents with carrying frequency of 2-5 kHz and frequency of modulation of 25-150 Hz. The results of this work can be interesting for developer of the electromyography and electrical stimulation systems, as well as for electrophysiologists and physiatrists.